2019
DOI: 10.1002/bbb.1997
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic model considering the heterogeneous nature of the enzyme hydrolysis of lignocellulosic materials

Abstract: In this work, a mathematical model is proposed to predict the kinetic behaviour of the enzymatic conversion of various types of lignocellulosic biomass into fermentable sugars. Digestion of the cellulosic polymers is carried out using enzymatic hydrolysis under different conditions. Unlike other kinetic models, published previously for this process, this one considers the heterogeneous nature of the process by which a solid, in the form of small particles, is decomposed to monosaccharides by the action of a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…As seen in Figure 3 A, RS concentration increases rapidly along the first 18 h in all the cases, while afterward the hydrolysis rate is very low. This is a consequence of the two stages (heterogeneous and homogeneous) that form the kinetics involved in the hydrolysis process [ 20 ]. The maximum RS concentration increased from 28.4 to 36.5 g·L −1 and the hydrolysis yield increased from 27.9% to 32.4% as the fermented solid mass rose from 5 to 10 g. Nevertheless, a similar maximum RS concentration was obtained when the fermented solid mass was 15 g (36.7 g·L −1 ) while the hydrolysis yield decreased until 29.7%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen in Figure 3 A, RS concentration increases rapidly along the first 18 h in all the cases, while afterward the hydrolysis rate is very low. This is a consequence of the two stages (heterogeneous and homogeneous) that form the kinetics involved in the hydrolysis process [ 20 ]. The maximum RS concentration increased from 28.4 to 36.5 g·L −1 and the hydrolysis yield increased from 27.9% to 32.4% as the fermented solid mass rose from 5 to 10 g. Nevertheless, a similar maximum RS concentration was obtained when the fermented solid mass was 15 g (36.7 g·L −1 ) while the hydrolysis yield decreased until 29.7%.…”
Section: Resultsmentioning
confidence: 99%
“…This parameter combines the maximum amount of sugar produced and the rate of production ( ). The regression coefficient (r 2 ) of the experimental data to the kinetic model of Caro et al [ 20 ] is also shown.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the viability of the scale-up of technologies to commercial scale can be aided by conditional and economic optimisation of the system via extensive process modelling e.g. models for the enzymatic hydrolysis of lignocellulose such as the modified Holtzapple-Caram-Humphrey-1 kinetic model [6], a kinetic model considering heterogeneity [7] or mathematical modelling. [8] One potential source of biomass for biorefineries is draff, also known as spent grain, which is produced as a by-product from the brewing and distilling industries.…”
Section: Introductionmentioning
confidence: 99%
“…The pretreatment of food waste biomass generally produces a size distribution that should be considered as an influential factor over enzymatic hydrolysis. Substrate particle size affects the overall rate of the hydrolysis process [96], given that this size impacts upon the efficiency of the substrate access of the enzymatic mixture, introducing mass transfer limitations in bigger particles. In addition, high solid presence in the reaction medium, an industrial tendency, increases viscosity and also affects the external and the internal mass transfer rate [97,98].…”
Section: Particle Size and Solid Loadingmentioning
confidence: 99%